Perlindungan Hukum Atas Data Pribadi Dalam Transaksi Pinjam Meminjam Uang Berbasis Teknologi Informasi - Prastyawan, Anang; Supriyono (Indonesian Journal of Law and Justice, 2024)
The purpose of this study is to find out and analyze the legal protection problems faced by the parties in the information technology-based loan-to-peer lending agreement. Knowing and analyzing solutions to overcome legal problems in lending agreements between parties based on information technology (peer to peer lending). The problem in this study is what are the legal protection problems faced by the parties in the information technology-based loan-lending agreement (peer to peer lending) and how to solve the legal problems in the information technology-based loan-lending agreement (peer to peer lending). The research method used in this study is doctrinal or normative legal research which is carried out by researching literature materials. This legal research uses a statue approach and a conceptual approach by analyzing existing legal problems and comparing them with the laws and legal regulations that govern them. The results of the study show that the legal protection problems faced by the parties in the information technology-based loan-lending agreement (peer to peer lending) include the problem of defamation by rogue debt collectors and personal data protection. These problems occur due to bad loans or debtors are unable to repay loans on time. Another problem is OJK Regulation No. 77/POJK.01/2016 concerning technology-based loan services, making it impossible for the authorities to follow up on these illegal fintech companies. The solution to overcome legal problems in lending agreements between parties based on information technology (peer to peer lending) requires adequate legal protection guarantees, which can be seen from the two mechanism improvements. Regarding the creation of agreements between Peer to Peer Lending parties, organizers and users must be in good faith in making agreements.